Evaluasi Kecukupan Nutrien Pakan Kelinci Bunting New Zealand White Pada Peternakan Kelinci di Kecamatan Nglegok Blitar - Anna Lidiyawati; Riska Faradila; Binti Khopsoh (Musamus Journal of Livestock Science, 2022)
Rabbit gestation production was expressed by litter size, there so many factor influence such as adequate nutrient. The aim of this study was to determine the nutrient adequacy of rabbit gestation in nglegok regency. The method used is survey dan data were analyzed descriptively. Twenty Seven rabbit gestation were observed in this study. There were three components in this study, which calculates the consumption of dry matter, crude protein, and total digestible nutrient in lactating dairy cows with reference to Permentan 2014. This research showed that consumption of dry matter, crude protein, and total digestible nutrien was 185,58 g, 31, 84 g and 12,21 g. In conclution, the ration given to rabbit gestation was sufficient Dry Matter, Crude Protein, and Total Digestible Nutrient.